Energy potential of household fats, oils and grease waste. (13th July 2021) - Collin, Thomas; Cunningham, Rachel; Deb, Melani; Villa, Raffaella; MacAdam, Jitka; Jefferson, Bruce
Abstract: In comparison to fats, oils and grease (FOG) found in commercial and industrial effluents, very little is known about FOG discharged at household level. To address this shortcoming, household FOG production was calculated following a year‐long monthly collection at 2.3 kg/year per household, equivalent to 0.8 kg/year per capita. In the United Kingdom, these numbers translate in an annual estimated FOG production of 62 380 tonnes. Physico‐chemical characterization of household FOG showed promising results for biodiesel production. Biomethane yield was measured at 875 mL CH4/g VSadded, twice as much that of sewage sludge, making it a desirable substrate for anaerobic digestion. It was thus estimated that energy recovery from household FOG through anaerobic co‐digestion or biodiesel production could generate about 490 GWh/year in the United Kingdom. However, insights from participants revealed that most of this waste is currently not recovered, requiring the development of schemes fitting with households' routine to maximize collection rates.